2000
DOI: 10.1021/tx9902082
|View full text |Cite
|
Sign up to set email alerts
|

Role of Quinones in Toxicology

Abstract: Quinones represent a class of toxicological intermediates which can create a variety of hazardous effects in vivo, including acute cytotoxicity, immunotoxicity, and carcinogenesis. The mechanisms by which quinones cause these effects can be quite complex. Quinones are Michael acceptors, and cellular damage can occur through alkylation of crucial cellular proteins and/or DNA. Alternatively, quinones are highly redox active molecules which can redox cycle with their semiquinone radicals, leading to formation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

40
1,204
3
32

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 1,523 publications
(1,279 citation statements)
references
References 253 publications
40
1,204
3
32
Order By: Relevance
“…We have previously reported that benzoquinone 35 and its derivatives 36,37 induce DNA damage via the NADH-dependent redox cycle. Thus, catechol estrogens appear to cause DNA damage by a similar mechanism, as suggested by Bolton et al 11,38 Comparison of the abilities of 2-OHE 2 and 4-OHE 2 to cause DNA damage revealed that in the presence of Cu(II), 4-OHE 2 causes more extensive strand breaks in plasmid DNA than 2-OHE 2 . 25 2-OHE 2 and 4-OHE 2 induced Cu(II)-dependent oxidative DNA damage to a similar extent at low nanomolar concentrations, suggesting that they have comparable abilities to generate reactive oxygen species.…”
Section: Discussionsupporting
confidence: 53%
“…We have previously reported that benzoquinone 35 and its derivatives 36,37 induce DNA damage via the NADH-dependent redox cycle. Thus, catechol estrogens appear to cause DNA damage by a similar mechanism, as suggested by Bolton et al 11,38 Comparison of the abilities of 2-OHE 2 and 4-OHE 2 to cause DNA damage revealed that in the presence of Cu(II), 4-OHE 2 causes more extensive strand breaks in plasmid DNA than 2-OHE 2 . 25 2-OHE 2 and 4-OHE 2 induced Cu(II)-dependent oxidative DNA damage to a similar extent at low nanomolar concentrations, suggesting that they have comparable abilities to generate reactive oxygen species.…”
Section: Discussionsupporting
confidence: 53%
“…Quinone derivative compounds induce a broad spectrum of effects in humans and represent a class of toxicological intermediates, which may induce acute cytotoxicity, immunotoxicity, and carcinogenesis, and lead to cellular damage [1]. They can be formed from benzene or polycyclic aromatic hydrocarbons and are toxicologically important components of air pollution [2] and cigarette smoke [3].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, oxidative stress results from an imbalance between the generation of ROS and endogenous antioxidant systems. ROS are major sources of primary catalysts that initiate oxidation in vivo and in vitro and create oxidative stress which results in numerous diseases and disorders [1] such as cancer [2] , cardiovascular disease [3] , neural disorders [4] , Alzheimer's disease [5] , mild congnitive impairment [6] , Parkinson's disease [7] , alcohol induced liver disease [8] , ulcerative colitis [9] , ageing [10] , and atherosclerosis [11] .…”
Section: Introductionmentioning
confidence: 99%